A summons to Memphis - Taylor, Peter Hillsman 1917-1994 (Knopf, 1986)
When Phillip Carver is asked by his sisters to help avert their widower father's impending marriage to a younger women, he is forced to confront his domineering siblings, a controlling patriarch, and a flood of memories from his deeply troubled past.
Keywords: Families -- Tennessee -- Memphis -- Fiction; Memphis (Tenn.) -- Fiction; Domestic fiction